Design of a ULB Diamond Monopoly Antenna (Journal of Informatics and Mathematical Sciences, 2022)
In this paper a new diamond monopoly antenna consisting of a diamond patch fed by a CPW coplanar waveguide and matched at 50 Ω over a very wide frequency band is presented. Parametric studies are applied on this antenna to improve the desired bandwidth. The design is performed by the CST Microwave Studio software. The final antenna obtained can be used for Ultra Wide Band operation.